High-rare-earth-element-content magnesium alloy bar with strength and plasticity tension and compression homogeneity and preparation method thereof
By adding rare earth elements to magnesium alloy and adopting slow hot extrusion process, combining SF6 protection atmosphere, optimizing the composition and process parameters of magnesium alloy, the problem of asymmetric stretching and compression performance of magnesium alloy at room temperature is solved, and the problem of asymmetry in magnesium alloy is achieved. The preparation of magnesium alloy rods with strength and plastic tensioning has enhanced its application potential.
Patent Information
- Application Number
- CN202411355563.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Due to the close hexagonal structure of magnesium alloy, there is significant asymmetry in strength and plasticity under tension and compression conditions at room temperature, limiting its application range.
By adding Gd, Y, Zr, Ag and Nd elements to the magnesium alloy and adopting a slow hot extrusion process, dynamic recrystallization time is provided, tension asymmetry is reduced, combined with SF6 protection atmosphere to prevent oxidation, controlling alloy composition and Process parameters, optimize grain structure and mechanical properties.
The strength and plastic tensioning and compression of magnesium alloy are achieved, the tensioning and compression performance of the alloy is improved, the severe tensioning and compression properties of magnesium alloys are solved, and the application potential in aerospace and automobile fields is improved. .
Smart Images

Figure CN119220838A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a magnesium alloy with high rare earth content, in particular to a magnesium alloy bar with high rare earth content and isotropic strength and plasticity and a preparation method thereof, belonging to the field of metal material preparation. Background Art
[0002] Magnesium alloy is known as the lightest metal structural material and plays an irreplaceable role in weight reduction of equipment such as automobiles, 3C and aerospace. Magnesium alloy with added rare earth elements has higher high-temperature strength.
[0003] China's invention patent application "A heat treatment method for heat-resistant cast magnesium alloy materials" (CN201811041410.5) designs continuous homogenization and multi-stage aging treatment. In its embodiment, the room temperature tensile strength of the Mg-10.5Gd-2.5Y-1.5Nd-0.1Zn-0.5Zr alloy is 365MPa, the elongation is 4.5%, and the tensile strength at 300°C is 225MPa, and the elongation is 18%. However, since magnesium alloys are close-packed hexagonal structures, twins will be turned on to coordinate dislocation slip. At room temperature, tension and compression have different effects on twins, resulting in a more significant asymmetry in the strength and plasticity of magnesium alloys under tension and compression conditions. As a lightweight structural material, only the worst performance in tension or compression can be selected as the use standard, which limits the application of magnesium alloys.
[0004] Chinese invention patent application CN202311425543.3 discloses a method for preparing and processing magnesium alloys to eliminate tensile and compressive asymmetry. This patent prepares ultrafine grains by rapid solidification, which weakens the tensile and compressive asymmetry of magnesium alloys. Chinese invention patent application CN201310552197.5 discloses a processing method for improving the tensile and compressive asymmetry of magnesium alloys. This patent can obtain magnesium alloys with greatly improved strength and tensile and compressive asymmetry by torsion. However, the above patents only focus on the tensile and compressive symmetry of magnesium alloy strength, and do not study the difference in tensile and compressive elongation after fracture. Summary of the invention
[0005] In order to solve the problem of severe strength and plastic tension-compression asymmetry of magnesium alloy, the present invention designs a deformed rare earth magnesium alloy bar with added Gd, Y, Zr, Ag and Nd elements, which can meet the requirements of aerospace, automobile and other fields for lightweight magnesium alloy structural materials.
[0006] The second object of the present invention is to provide a method for preparing a magnesium alloy rod with high rare earth element content and isotropic plasticity in tension and compression, which provides sufficient dynamic recrystallization time for the alloy through slow hot extrusion, thereby reducing the severe tension and compression asymmetry of the magnesium alloy.
[0007] In order to achieve the above technical objectives, the present invention provides a method for preparing a magnesium alloy rod with high rare earth element content and isotropic strength and plasticity in tension and compression. The method comprises the following steps: weighing each component according to the designed magnesium alloy component ratio, and sequentially melting and casting magnesium, magnesium-gadolinium master alloy, magnesium-yttrium master alloy, silver, magnesium-zirconium master alloy and magnesium-neodymium master alloy under SF6 protective atmosphere to obtain an ingot; the ingot is homogenized and continuously extruded to obtain a magnesium alloy rod;
[0008] The magnesium alloy bar is composed of the following components by mass percentage: Gd: 10-12%, Y: 1-2%, Zr: 0.01-0.5%, Ag: 0.01-0.5%, Nd: 0.01-0.5%, and the total mass content of rare earth elements is ≥12%; impurity elements Al≤0.01%, Fe≤0.04%, Mn≤0.02%, the total content of impurity elements does not exceed 0.1%, and the rest is Mg. More preferably, Gd: 11.5-12%, Y: 1-1.7%, Zr: 0.01-0.37%, Ag: 0.01-0.5%, Nd: 0.01-0.39%, and the total mass content of rare earth elements is ≥12%; impurity elements Al≤0.01%, Fe≤0.04%, Mn≤0.02%, the total content of impurity elements does not exceed 0.1%, and the rest is Mg. In a further preferred alloy composition range, the prepared magnesium alloy rod has optimal tensile and compressive isotropy, and also has high plasticity and strength.
[0009] The key to the technical solution of the present invention lies in the combination of the design of the composition and the preparation method, specifically: the present invention can improve the mechanical properties of the magnesium alloy by adding Gd and Y elements to the magnesium alloy, and at the same time weaken the basal surface texture (0001 basal surface) after extrusion deformation, reduce anisotropy and tension-compression asymmetry, while Ag and Zr elements can refine the alloy grains in the casting stage, and the addition of trace Nd elements can improve the mechanical properties of the magnesium alloy in the casting stage. At the same time, the synergistic addition of Gd, Y and Nd rare earth elements can improve the room temperature strength of the magnesium alloy. In addition, the composition needs to be combined with the control of the process parameters of the present invention. The preparation of the present invention mainly adopts slow hot extrusion to provide sufficient dynamic recrystallization time for the alloy. At the same time, by introducing shear stress during the extrusion process, the dislocation density inside the grain can be increased, and the grain orientation can be changed, thereby breaking the basal surface texture in the magnesium alloy.
[0010] The inventors found that using SF6 as a protective atmosphere during the preparation process can effectively prevent the oxidation of magnesium alloys during the smelting process. SF6 can form a dense protective film on the surface of the magnesium alloy, mainly composed of MgO and MgF2, which can effectively isolate the contact between oxygen and the magnesium alloy, thereby slowing down or preventing the oxidation of magnesium.
[0011] At the same time, in the present invention, the dosage of each metal element also needs to be controlled, especially the dosage of the three elements Zr, Ag and Nd. If the dosage is too high, the elongation of the magnesium alloy will be seriously reduced.
[0012] As a preferred solution, the purity of the magnesium and silver is greater than 99.9%.
[0013] As a preferred solution, during the smelting process, magnesium is first added and the temperature is raised to 770-800°C, and then magnesium-gadolinium master alloy, magnesium-yttrium master alloy and silver are added. After they are completely melted, magnesium-zirconium master alloy and magnesium-neodymium master alloy are added and kept warm for 30-40 minutes, and refined at 750-760°C.
[0014] As a preferred solution, the casting is performed after standing for 30 to 40 minutes after smelting; the pull-down speed of the casting is 2 to 10 cm / min. The present invention can fully remove the gas in the melt by standing for a period of time after smelting, improve the microstructure and macroscopic properties of the magnesium alloy, and reduce the pores and micro-porosity in the casting. As a preferred solution, the conditions for the homogenization treatment are: first heating to 300 to 320°C and keeping warm for 10 to 12 hours, then heating to 480 to 500°C and keeping warm for 10 to 12 hours, and then immediately water quenching.
[0015] As a preferred solution, the conditions for continuous extrusion are: temperature of 400-450°C, heat preservation for 20-30 minutes, continuous extrusion ratio greater than 10, extrusion speed of 0.1-0.2 m / s, and water quenching immediately after continuous extrusion. Within the alloy composition and dosage range of the present invention, increasing the extrusion ratio can further refine the alloy grains and improve the mechanical properties; while slow extrusion is conducive to full dynamic recrystallization during the extrusion process to obtain a uniform structure without distortion. At the same time, the extrusion temperature affects the speed of dynamic recrystallization of the alloy, and appropriately increasing the extrusion temperature is conducive to dynamic recrystallization. It is further preferred that the extrusion ratio is 16-20:1 and the temperature is 420-450°C. It is further preferred that the extrusion ratio is 20:1. Within a further preferred range, the tensile-compression-extension yield strength ratio of the alloy is 1.08-1.12, and the tensile-compression elongation ratio is 1.04-1.29.
[0016] The present invention also provides a magnesium alloy bar with high rare earth element content and isotropic strength and plasticity, which is obtained by the above preparation method. The magnesium alloy bar obtained by the preparation method and composition design of the present invention has Mg5Gd precipitation phase strengthening alloy, Mg 24 Precipitation phases such as Y5 and Mg3Ag can also effectively strengthen the alloy.
[0017] As a preferred solution, the grain size of the high rare earth element content magnesium alloy rod of the present invention is 2.4-3.2 μm. The grain size of the magnesium alloy rod obtained by the preparation method of the present invention is small and the distribution range is narrow, and the fine grains can effectively hinder the movement of dislocations and promote grain boundary sliding as a mechanism of plastic deformation, thereby bringing a dual improvement in strength and plasticity to the magnesium alloy.
[0018] As a preferred solution, the tension-compression-elongation yield strength ratio is 0.91-1.12, and the tension-compression elongation after fracture ratio is 1.04-1.29.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The ratio of the tensile-compressive yield strength of the alloy of the present invention at room temperature can reach up to 1.08, and the ratio of the tensile-compressive elongation after fracture can reach up to 1.04.
[0021] (2) The present invention reduces the basal texture by continuous extrusion. Continuous extrusion can break the basal texture (0001 basal plane) in the magnesium alloy by introducing shear stress during the extrusion process. During the extrusion process, the material undergoes severe plastic deformation, which increases the dislocation density inside the grains and changes the grain orientation, thereby weakening the dominance of the basal texture. In addition, during the long-term extrusion process, the material undergoes complete dynamic recrystallization, which helps to refine the grains and further weaken the basal texture, thereby increasing the plasticity, strength and deformation degree of the magnesium alloy, and solving the problem of severe tension and compression asymmetry of the magnesium alloy.
[0022] (3) In the present invention, Zr, Ag and a trace amount of Nd are added to the components through continuous extrusion, so that a large number of recrystallized grains can be introduced into the alloy, and the average grain size is about 2.4 μm, which significantly improves the mechanical properties of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a typical SEM image after homogenization treatment of the present invention.
[0024] Figure 2 This is the EBSD result of the alloy in Example 1 of the present invention.
[0025] Figure 3 This is a grain size distribution diagram of the alloy of Example 1 of the present invention.
[0026] Figure 4 The room temperature tensile and compressive stress-strain curves of the alloy in Example 1 of the present invention.
[0027] Figure 5 These are room temperature tensile and compression fracture photos of the alloy of Example 1 of the present invention.
[0028] Figure 6 The room temperature tensile and compressive stress-strain curves of the alloy in Example 2. DETAILED DESCRIPTION
[0029] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner in conjunction with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.
[0030] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0031] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.
[0032] Example 1
[0033] (1)Alloy composition
[0034] The alloy composition (mass fraction) is: Gd: 11.5%, Y: 1.7%, Zr: 0.37%, Ag: 0.5%, Nd: 0.39%, impurity elements Al≤0.01%, Fe≤0.04%, Mn≤0.02%, and the rest is Mg.
[0035] (2) Alloy casting
[0036] The weighed alloy is placed in a drying oven, and the temperature of the drying oven is set to 150°C. Then pure magnesium is added, and then the temperature is raised to about 770°C, and Mg-30Gd, Mg-30Y and pure silver are added. After they are completely melted, Mg-20Zr and Mg-20Nd are added. After keeping the temperature for 30 minutes, they are refined at 750°C. After refining, they are left to stand for 30 minutes, and finally poured into a steel mold. The entire smelting process is carried out under SF6 protective atmosphere, and the casting pull-down speed is 10cm / min. The alloy composition meets the above composition requirements.
[0037] (3) Alloy homogenization treatment
[0038] The ingot was placed in a resistance furnace and heated to 320°C and kept at this temperature for 12 hours, then heated to 500°C and kept at this temperature for 12 hours, and then quenched by water cooling.
[0039] (4) Alloy continuous extrusion
[0040] The resistance furnace was heated to 450°C, and after the temperature was stabilized for 30 minutes, the homogenized annealed alloy was placed in the resistance furnace and kept warm for 20 minutes. Then extrusion was started with an extrusion speed of 0.1 m / s and an extrusion ratio of 20:1. After extrusion, it was immediately water-cooled and quenched to obtain the alloy.
[0041] (5) Mechanical properties
[0042] After homogenization and extrusion at 450℃ (20:1), the tensile yield strength of the alloy in this example is 288MPa at room temperature, and the elongation after fracture is 19.0%. The compressive yield strength at room temperature is 266MPa, and the elongation after fracture is 18.2%. The ratio of tensile and compressive yield strength is 1.08, and the ratio of tensile and compressive elongation after fracture is 1.04.
[0043] The EBSD results of the alloy prepared in Example 1 are shown in Figure 2 The EBSD inverse pole figure shows that there are a large number of dynamically recrystallized grains in the alloy, and there are no narrow and long deformed grains. The pole figure shows that the alloy does not have a strong basal texture after extrusion. The grain size distribution diagram of the alloy prepared in Example 1 is shown in Figure 3 As can be seen from the figure, the average grain size of the alloy prepared by the present invention is 2.4 μm, the grains are fine, and the grain distribution range of the alloy is narrow.
[0044] Example 2
[0045] (1)Alloy composition
[0046] The alloy composition (mass fraction) is: Gd: 11.5%, Y: 1.7%, Zr: 0.37%, Ag: 0.5%, Nd: 0.39%, impurity elements Al≤0.01%, Fe≤0.04%, Mn≤0.02%, and the rest is Mg.
[0047] (2) Alloy casting
[0048] The weighed alloy is placed in a drying oven, and the temperature of the drying oven is set to 150°C. Then pure magnesium is added, and then the temperature is raised to about 770°C, and Mg-30Gd, Mg-30Y and pure silver are added. After they are completely melted, Mg-20Zr and Mg-20Nd are added. After keeping the temperature for 30 minutes, they are refined at 750°C. After refining, they are left to stand for 30 minutes, and finally poured into a steel mold. The entire smelting process is carried out under SF6 protective atmosphere, and the casting pull-down speed is 10cm / min. The alloy composition meets the above composition requirements.
[0049] (3) Alloy homogenization treatment
[0050] The ingot was placed in a resistance furnace and heated to 320°C and kept at this temperature for 12 hours, then heated to 500°C and kept at this temperature for 12 hours, and then quenched by water cooling.
[0051] (4) Alloy continuous extrusion
[0052] The resistance furnace was heated to 450°C, and after the temperature was stabilized for 30 minutes, the homogenized annealed alloy was placed in the resistance furnace and kept warm for 20 minutes. Then extrusion was started with an extrusion speed of 0.1 m / s and an extrusion ratio of 16:1. After extrusion, it was immediately water-cooled and quenched to obtain the alloy.
[0053] (5) Mechanical properties
[0054] After homogenization and extrusion at 450℃ (16:1), the tensile yield strength of the alloy in this example is 284MPa at room temperature, and the elongation after fracture is 17.3%. The compressive yield strength at room temperature is 260MPa, and the elongation after fracture is 13.8%. The tensile-compressive yield strength ratio is 1.09, and the tensile-compressive elongation ratio is 1.25.
[0055] Example 3
[0056] (1)Alloy composition
[0057] The alloy composition (mass fraction) is: Gd: 11.5%, Y: 1.7%, Zr: 0.37%, Ag: 0.5%, Nd: 0.39%, impurity elements Al≤0.01%, Fe≤0.04%, Mn≤0.02%, and the rest is Mg.
[0058] (2) Alloy casting
[0059] The weighed alloy is placed in a drying oven, and the temperature of the drying oven is set to 150°C. Then pure magnesium is added, and then the temperature is raised to about 770°C, and Mg-30Gd, Mg-30Y and pure silver are added. After they are completely melted, Mg-20Zr and Mg-20Nd are added. After keeping the temperature for 30 minutes, they are refined at 750°C. After refining, they are left to stand for 30 minutes, and finally poured into a steel mold. The entire smelting process is carried out under SF6 protective atmosphere, and the casting pull-down speed is 10cm / min. The alloy composition meets the above composition requirements.
[0060] (3) Alloy homogenization treatment
[0061] The ingot was placed in a resistance furnace and heated to 320°C and kept at this temperature for 12 hours, then heated to 500°C and kept at this temperature for 12 hours, and then quenched by water cooling.
[0062] (4) Alloy continuous extrusion
[0063] The resistance furnace was heated to 450°C, and after the temperature was stabilized for 30 minutes, the homogenized annealed alloy was placed in the resistance furnace and kept warm for 20 minutes. Then extrusion was started with an extrusion speed of 0.1 m / s and an extrusion ratio of 10:1. After extrusion, it was immediately water-cooled and quenched to obtain the alloy.
[0064] (5) Mechanical properties
[0065] After homogenization and extrusion at 450℃ (10:1), the tensile yield strength of the alloy in this example is 240MPa at room temperature, and the elongation after fracture is 12.6%. The compressive yield strength at room temperature is 213MPa, and the elongation after fracture is 9.8%. The ratio of tensile and compressive yield strength is 1.12, and the ratio of tensile and compressive elongation after fracture is 1.29.
[0066] Example 4
[0067] (1)Alloy composition
[0068] The alloy composition (mass fraction) is: Gd: 11.5%, Y: 1.7%, Zr: 0.37%, Ag: 0.5%, Nd: 0.39%, impurity elements Al≤0.01%, Fe≤0.04%, Mn≤0.02%, and the rest is Mg.
[0069] (2) Alloy casting
[0070] The weighed alloy is placed in a drying oven, and the temperature of the drying oven is set to 150°C. Then pure magnesium is added, and then the temperature is raised to about 770°C, and Mg-30Gd, Mg-30Y and pure silver are added. After they are completely melted, Mg-20Zr and Mg-20Nd are added. After keeping the temperature for 30 minutes, they are refined at 750°C. After the refining is completed, they are left to stand for 30 minutes, and finally poured into a steel mold. The entire smelting process is carried out under SF6 protective atmosphere, and the casting pull-down speed is 10cm / min. The alloy composition meets the above composition requirements.
[0071] (3) Alloy homogenization treatment
[0072] The ingot was placed in a resistance furnace and heated to 320°C and kept at this temperature for 12 hours, then heated to 500°C and kept at this temperature for 12 hours, and then quenched by water cooling.
[0073] (4) Alloy continuous extrusion
[0074] The resistance furnace was heated to 400°C, and after the temperature was stabilized for 30 minutes, the homogenized annealed alloy was placed in the resistance furnace and kept warm for 20 minutes. Then extrusion was started with an extrusion speed of 0.1 m / s and an extrusion ratio of 20:1. After extrusion, it was immediately water-cooled and quenched to obtain the alloy.
[0075] (5) Mechanical properties
[0076] After homogenization and extrusion at 400℃ (10:1), the tensile yield strength of the alloy in this example is 262MPa at room temperature, and the elongation after fracture is 17.6%. The compressive yield strength at room temperature is 288MPa, and the elongation after fracture is 13.9%. The ratio of tensile and compressive yield strength is 0.91, and the ratio of tensile and compressive elongation after fracture is 1.27.
[0077] Example 5
[0078] (1)Alloy composition
[0079] The alloy composition (mass fraction) is: Gd: 10.5%, Y: 1.8%, Zr: 0.45%, Ag: 0.5%, Nd: 0.41%, impurity elements Al≤0.01%, Fe≤0.04%, Mn≤0.02%, and the rest is Mg.
[0080] (2) Alloy casting
[0081] The weighed alloy is placed in a drying oven, and the temperature of the drying oven is set to 150°C. Then pure magnesium is added, and then the temperature is raised to about 770°C, and Mg-30Gd, Mg-30Y and pure silver are added. After they are completely melted, Mg-20Zr and Mg-20Nd are added. After keeping the temperature for 30 minutes, they are refined at 750°C. After refining, they are left to stand for 30 minutes, and finally poured into a steel mold. The entire smelting process is carried out under SF6 protective atmosphere, and the casting pull-down speed is 10cm / min. The alloy composition meets the above composition requirements.
[0082] (3) Alloy homogenization treatment
[0083] The ingot was placed in a resistance furnace and heated to 320°C and kept at this temperature for 12 hours, then heated to 500°C and kept at this temperature for 12 hours, and then quenched by water cooling.
[0084] (4) Alloy continuous extrusion
[0085] The resistance furnace was heated to 450°C, and after the temperature was stabilized for 30 minutes, the homogenized annealed alloy was placed in the resistance furnace and kept warm for 20 minutes. Then extrusion was started with an extrusion speed of 0.2 m / s and an extrusion ratio of 20:1. After extrusion, it was immediately water-cooled and quenched to obtain the alloy.
[0086] (5) Mechanical properties
[0087] After homogenization and extrusion at 450℃ (20:1), the tensile yield strength of the alloy in this example is 253MPa at room temperature, and the elongation after fracture is 16.3%. The compressive yield strength at room temperature is 213MPa, and the elongation after fracture is 9.9%. The tensile-compressive yield strength ratio is 1.19, and the tensile-compressive elongation ratio after fracture is 1.65.
[0088] Example 6
[0089] (1)Alloy composition
[0090] The alloy composition (mass fraction) is: Gd: 10.5%, Y: 1.8%, Zr: 0.45%, Ag: 0.5%, Nd: 0.41%, impurity elements Al≤0.01%, Fe≤0.04%, Mn≤0.02%, and the rest is Mg.
[0091] (2) Alloy casting
[0092] The weighed alloy is placed in a drying oven, and the temperature of the drying oven is set to 150°C. Then pure magnesium is added, and then the temperature is raised to about 770°C, and Mg-30Gd, Mg-30Y and pure silver are added. After they are completely melted, Mg-20Zr and Mg-20Nd are added. After keeping warm for 30 minutes, they are refined at 750°C. After refining, they are left to stand for 40 minutes, and finally poured into a steel mold. The entire smelting process is carried out under SF6 protective atmosphere, and the casting pull-down speed is 10cm / min. The alloy composition meets the above composition requirements.
[0093] (3) Alloy homogenization treatment
[0094] The ingot was placed in a resistance furnace and heated to 320°C and kept at this temperature for 12 hours, then heated to 500°C and kept at this temperature for 12 hours, and then quenched by water cooling.
[0095] (4) Alloy continuous extrusion
[0096] The resistance furnace was heated to 400°C. After the temperature stabilized for 30 minutes, the homogenized annealed alloy was placed in the resistance furnace and kept warm for 20 minutes. Then extrusion was started with an extrusion speed of 0.1 m / s and an extrusion ratio of 20:1. After extrusion, the alloy was immediately water-cooled and quenched.
[0097] (5) Mechanical properties
[0098] After homogenization and extrusion at 400℃ (20:1), the tensile yield strength of the alloy in this example is 238MPa at room temperature, and the elongation after fracture is 13.3%. The compressive yield strength at room temperature is 256MPa, and the elongation after fracture is 10.6%. The tensile-compressive yield strength ratio is 0.92, and the tensile-compressive elongation ratio after fracture is 1.25.
[0099] Comparative Example 1
[0100] The only difference between this comparative example and Example 1 is that the mass fraction of Gd in the magnesium alloy is replaced with 8.5%, and the other components, preparation steps and conditions are the same to obtain an alloy.
[0101] Comparative Example 2
[0102] The only difference between this comparative example and Example 1 is that the extrusion speed is increased to 0.5 m / s, and the other components, steps and conditions are the same to obtain an alloy.
[0103] The mechanical properties of the alloys prepared in Examples 1 to 6 and Comparative Examples 1 to 2 are shown in Table 1.
[0104] Table 1
[0105]
[0106] Note: The test data in Table 1 are tested at room temperature.
[0107] From the data comparison of Table 1, it can be seen that when the alloy composition of Examples 1 to 3 remains unchanged, the alloy grains can be further refined as the extrusion ratio increases, and the strength and plasticity of the magnesium alloy are increased. At the same time, the effect of the extrusion ratio on the tensile and compressive elongation ratio of the plastic is particularly significant. From the data comparison of Example 1 and Example 4, it can be seen that when the alloy composition remains unchanged, the dynamic recrystallization rate of the alloy slows down when the extrusion temperature is reduced, resulting in an increase in the tensile and compressive elongation ratio of the magnesium alloy. From the data comparison of Example 5 and Example 1, when the amount of Gd, Y, Zr and Nd in the alloy is changed and the extrusion speed is increased, the strength and plasticity of the magnesium alloy will decrease, especially the tensile and compressive symmetry of the plasticity. While comparing the data of Comparative Example 1 and Example 1, when the Gd content in the alloy is reduced, the overall performance of the magnesium alloy is significantly reduced. While comparing the data of Comparative Example 2 and Example 1, when the extrusion speed is increased, there is no obvious effect on the tensile and compressive symmetry of the strength of the alloy, but the tensile and compressive symmetry of the plasticity of the alloy will be significantly reduced.
Claims
1. A method for preparing a magnesium alloy bar with high rare earth element content and isotropic strength and plasticity in tension and compression, characterized in that: According to the designed magnesium alloy component ratio, each component is weighed, and magnesium, magnesium-gadolinium master alloy, magnesium-yttrium master alloy, silver, magnesium-zirconium master alloy and magnesium-neodymium master alloy are sequentially melted and cast under SF6 protective atmosphere to obtain ingots; the ingots are homogenized and continuously extruded to obtain magnesium alloy rods; The magnesium alloy rod is composed of the following components by mass percentage: Gd: 10-12%, Y: 1-2%, Zr: 0.01-0.5%, Ag: 0.01-0.5%, Nd: 0.01-0.5%, and the total mass content of rare earth elements is ≥12%; impurity elements Al≤0.01%, Fe≤0.04%, Mn≤0.02%, the total content of impurity elements does not exceed 0.1%, and the rest is Mg.
2. The method for preparing a magnesium alloy bar with high rare earth element content and isotropic strength and plasticity in tension and compression according to claim 1, characterized in that: The purity of the magnesium and silver is greater than 99.9%.
3. The method for preparing a magnesium alloy bar with high rare earth element content and isotropic plasticity in tension and compression according to claim 2, characterized in that: In the smelting process, magnesium is first added and the temperature is raised to 770-800° C., and then magnesium-gadolinium master alloy, magnesium-yttrium master alloy and silver are added. After they are completely melted, magnesium-zirconium master alloy and magnesium-neodymium master alloy are added and kept warm for 30-40 minutes, and refined at 750-760° C.
4. A method for preparing a magnesium alloy bar with high rare earth element content and isotropic strength and plasticity in tension and compression according to any one of claims 1 to 3, characterized in that: After the smelting, the mixture is allowed to stand for 30 to 40 minutes before casting; the pulling speed of the casting is 2 to 10 cm / min.
5. The method for preparing a magnesium alloy bar with high rare earth element content and isotropic strength and plasticity in tension and compression according to claim 4, characterized in that: The homogenization treatment conditions are: firstly heating to 300-320°C and keeping the temperature for 10-12h, then heating to 480-500°C and keeping the temperature for 10-12h, and then immediately water quenching.
6. The method for preparing a magnesium alloy bar with high rare earth element content and isotropic strength and plasticity in tension and compression according to claim 1, characterized in that: The conditions for continuous extrusion are: temperature of 400-450° C., heat preservation for 20-30 minutes, continuous extrusion ratio greater than 10, extrusion speed of 0.1-0.2 m / s, and water quenching immediately after continuous extrusion.
7. A magnesium alloy bar with high rare earth element content and isotropic strength and plasticity in tension and compression, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 6.
8. A magnesium alloy bar with high rare earth element content and isotropic strength and plasticity in tension and compression according to claim 7, characterized in that: The tensile-compression-extension yield strength ratio is 0.91-1.12, the tensile-compression elongation after fracture ratio is 1.04-1.29, and the grain size is 2.4-3.2 μm.
Citation Information
Patent Citations
Ultrahigh-strength rare earth-magnesium alloy board and preparation method thereof
CN102337441A
Mg-Gd-Y-Nd high-strength and high-toughness rare earth magnesium alloy and preparation method thereof
CN112410632A
High-rare-earth-element-content magnesium alloy with both room-temperature strength and high-temperature strength and preparation method thereof
CN117144217A
